Dietary natural products as epigenetic modifiers in aging-associated inflammation and disease. Issue 5 (29th January 2020) - Evans, Levi W.; Stratton, Matthew S.; Ferguson, Bradley S.
Abstract : Chronic, low-grade inflammation is linked to aging and has been termed "inflammaging". Abstract : Covering: up to 2020 Chronic, low-grade inflammation is linked to aging and has been termed "inflammaging". Inflammaging is considered a key contributor to the development of metabolic dysfunction and a broad spectrum of diseases or disorders including declines in brain and heart function. Genome-wide association studies (GWAS) coupled with epigenome-wide association studies (EWAS) have shown the importance of diet in the development of chronic and age-related diseases. Moreover, dietary interventions e.g. caloric restriction can attenuate inflammation to delay and/or prevent these diseases. Common themes in these studies entail the use of phytochemicals (plant-derived compounds) or the production of short chain fatty acids (SCFAs) as epigenetic modifiers of DNA and histone proteins. Epigenetic modifications are dynamically regulated and as such, serve as potential therapeutic targets for the treatment or prevention of age-related disease. In this review, we will focus on the role for natural products that include phytochemicals and short chain fatty acids (SCFAs) as regulators of these epigenetic adaptations. Specifically, we discuss regulators of methylation, acetylation and acylation, in the protection from chronic inflammation driven metabolic dysfunction and deterioration of neurocognitive and cardiac function.